Holotrichia burmeisteri Brenske, 1892 and allies (Coleoptera: Scarabaeidae: Melolonthinae: Rhizotrogini): a tale of four genera and four countries - Allsopp, Peter G. (Zootaxa, 2025)
The Palauan species Holotrichia burmeisteri Brenske, 1892 is shown to be a member of the Rhizotrogini and, hence, incorrectly placed in the eastern Australian genus Metatrogus Britton, 1978 (Melolonthini). Comparison with another species described from Palau shows that H. burmeisteri is a senior synonym of Lepidiota carolinensis Arrow, 1939 (new synonymy). That species and two other closely related species also described from Palau, L. dybasi Gordon, 1979 and L. furtiva Gordon, 1979, are transferred to Cheberdord Allsopp, new genus. The presumed occurrence of C. burmeisteri in the Philippines and Australia is considered extremely doubtful, and the record from Guam is based on one individual transported in luggage. Lectotypes are designated for Holotrichia burmeisteri Brenske, 1892 and Lepidiota carolinensis Arrow, 1939.